Development Of Medical Social Work Practice In Malaysia: A Historical Perspective - Lee, Elsie Lee @ Pek Neo (2011)

(untitled)
This study adopted a qualitative design and an inductive strategy to collect primary data through tape recorded interviews with 15 respondents who once held or are still holding, the posts of medical social workers. The framework of analysis was based on four areas, i.e., the medical social work practice, its institutional context, social work education and professional standing, over three different time frames which are 1950-1969, 1970-1989 and 1990-2010. The findings showed that the practice had developed out of a need for supportive psychosocial services in the aftermath of World War II, and professional training was a prerequisite for practice during the first three decades. However a change in intake policy beginning in the mid - 1980s saw the recruitment of graduates without social work qualifications into both public and university hospitals, followed by the secondment of untrained welfare assistants into public hospitals in the late 1980s, and the intake of counsellors into public hospitals in the late 1990s. The findings showed that by 2010 these events had contributed significantly to a subsequent diminishing emphasis in the professional role and tasks of counselling and psychosocial support, and a significant increase in the task of social assessments for financial problems, which narrowed perception of medical social work to being mere welfare assistance. This perception within the hospital institution still persists but, in the last five years the Ministry of Health has taken clear steps to reprofessionalise medical social work practice through the enactment of an Allied Health Professions Bill which is in the process of being drafted